Motivasi dalam Pembelajaran Mate Motivasi dalam Pembelajaran Matematika Siswa di SMK Teladan Tanah Jawa: Motivasi dalam Pembelajaran Matematika Siswa di SMK Teladan Tanah Jawa - Gayus Simarmata; Christa Voni Roulina Sinaga (PendIPA Journal of Science Education, 2023)
Learning mathematics in vocational high school (SMK) is not always easy. There are times when vocational high school mathematics teachers complain about learning problems. This study aims to determine learning motivation and its contribution to student learning outcomes at SMK Nusantara Tanah Jawa. The research method used was a survey method with correlational analysis, with a total sample of 79 people. The data collection techniques used were interviews, questionnaires and documentation. From the results of the research, it was obtained; that the measure of student motivation was 64.61, while the learning outcomes were 64.61 (complete). A 54.80% of students' mathematics learning outcomes were determined by their learning motivation, with the regression equation Y' = 9.86 + 0.86X. The magnitude of the contribution of learning motivation to learning outcomes does not determine the level of learning outcomes.